Answer:
Option A is correct.i.e, [tex]f(x)=4\,sin(x-\frac{\pi}{2})[/tex]
Step-by-step explanation:
We are given with a graph .
A points from graph which satisfies it = [tex](\frac{\pi}{2},0)\:,\:(\pi,4)\:,\:(\frac{3\pi}{2},0)\:,\:(2\pi,0)[/tex]
We check which equation satisfy points.
Option A:
[tex]f(x)=4\,sin(x-\frac{\pi}{2})[/tex]
Let, [tex]y=4\,sin(x-\frac{\pi}{2})[/tex]
we have [tex](\frac{\pi}{2},0)[/tex]
LHS = y = 0
[tex]RHS=4\,sin(x-\frac{\pi}{2})=4\,sin(\frac{\pi}{2}-\frac{\pi}{2})=4\,sin\,0=4\times0=0[/tex]
LHS = RHS
Thus, This Option is correct.
Option B:
[tex]f(x)=4\,cos(x-\frac{\pi}{2})[/tex]
Let, [tex]y=4\,cos(x-\frac{\pi}{2})[/tex]
we have [tex](\frac{\pi}{2},0)[/tex]
LHS = y = 0
[tex]RHS=4\,cos(x-\frac{\pi}{2})=4\,cos(\frac{\pi}{2}-\frac{\pi}{2})=4\,cos\,0=4\times1=4[/tex]
LHS ≠ RHS
Thus, This Option is not correct.
Option C:
[tex]f(x)=4\,sin(x-\frac{\pi}{2})+1[/tex]
Let, [tex]y=4\,sin(x-\frac{\pi}{2})+1[/tex]
we have [tex](\frac{\pi}{2},0)[/tex]
LHS = y = 0
[tex]RHS=4\,sin(x-\frac{\pi}{2})+1=4\,sin(\frac{\pi}{2}-\frac{\pi}{2})+1=4\,sin\,0+1=4\times0+1=1[/tex]
LHS ≠ RHS
Thus, This Option is not correct.
Option D:
[tex]f(x)=4\,cos(x-\frac{\pi}{2})+1[/tex]
Let, [tex]y=4\,cos(x-\frac{\pi}{2})+1[/tex]
we have [tex](\frac{\pi}{2},0)[/tex]
LHS = y = 0
[tex]RHS=4\,cos(x-\frac{\pi}{2})+1=4\,cos(\frac{\pi}{2}-\frac{\pi}{2})+1=4\,cos\,0+1=4\times1+1=5[/tex]
LHS ≠ RHS
Thus, This Option is not correct.
Therefore, Option A is correct.i.e, [tex]f(x)=4\,sin(x-\frac{\pi}{2})[/tex]